Investigating the Perceptions, Use, and Impact of Open Textbooks: A survey of Post-Secondary Students in British Columbia - Jhangiani, Rajiv Sunil; Jhangiani, Surita (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
Unrelenting increases in the price of college textbooks have prompted the development and adoption of open textbooks, educational resources that are openly licensed and available to students free of cost. Although several studies have investigated U.S. students’ perceptions and use of open textbooks, there are no published studies of this kind in Canada. Similarly, although the negative impact of commercial textbook costs on student outcomes is well documented within the United States, it is unknown whether these trends generalize to the Canadian post-secondary context. The present study involves a survey of 320 post-secondary students in British Columbia enrolled in courses using an open textbook during the Spring 2015, Summer 2015, and Fall 2015 semesters. The survey investigates students’ textbook purchasing behaviours, including whether, where, and in what format(s) they purchase and access their required textbooks; the negative impact of textbook costs on their course enrolment, persistence, and performance; how they access and use their open textbook, including their format preferences and study habits; and their perceptions of their open textbook, including its quality and what features they like and dislike. The study’s strengths and limitations are discussed, along with recommendations for future research.